The Expanding Role of the Oncology Pharmacist - Lisa M. Holle; Eve M. Segal; Kate D. Jeffers (MDPI AG, 2020)
Although oncology pharmacists have been involved in the care of cancer patients for over 50 years, the role of the oncology pharmacist continues to expand. Initially, pharmacists were primarily based within either an inpatient or outpatient pharmacy setting and their work focused on providing the necessary safety checks to dispense cancer-related medications. With technology freeing up pharmacists from dispensing functions and advanced training in direct patient care (e.g., oncology residency, oncology fellowship), the oncology pharmacist was able to provide direct patient care at the bedside or within the clinic where treatment decisions are made by the healthcare team. In fact, they have become integral members of the healthcare team. This Issue describes several expanding roles of oncology pharmacists in stem cell transplant, hematology, gastrointestinal oncology, and precision genomics, as well as oncology pharmacists preventing a reduction in cancer patient visits as the oncology physician shortage occurs. Oncology pharmacists are an integral part of the cancer care team; their value has been documented in several studies, and is highlighted in this Issue. We encourage the profession to continue to document their value so that one day each patient can have an oncology pharmacist as part of their cancer care team.